Training on making creative learning media using the canva application for MI and MTs Al-Mu'minin Kendari Teachers - Fathur Rahman Rustan; Muhammad Syaiful; Rahmat Karim; Mutmainnah Muchtar; Jayanti Yusmah Sari; Phradiansah Phradiansah; Indar Ismail Jamaluddin; Suharsono Bantun; Nur Fajriah Muchlis; Yuwanda Purnamasari Pasrun; La Ode Hasnuddin S Sagala (Universitas Muhammadiyah Magelang, 2022)
Attractive learning media has become a necessity for teachers at all levels of education. For this reason, educators need to improve their competence in making good learning media. However, there are still many teachers who are not familiar with using technology to support their teaching and learning activities. As felt by MI and MTs AL-Mu'minin Kendari teachers who still find it difficult to make interesting and creative learning media. This service activity aims to improve the ability of teachers to create interesting media using the Canva application. The stages carried out in this activity are (1) coordinating with the school and identifying the needs of the target audience; (2) carry out community service activities with lecture, question and answer methods, and guided practice; and (3) evaluate and assign independent assignments. The results of this program showed an increase in teacher skills in making interesting learning media as seen from the independent assignments that were collected.